Faḫr ad-Dīn ar-Rāzī, Ibn al-Hayṯam and Aristotelian Science: Essentialism versus Phenomenalism in Post-Classical Islamic Thought - Ibrahim, Bilal (Oriens, 2013)
This article examines Avicenna’s view of Aristotelian demonstrative science and the emergence of a competing philosophical system in the works of Faḫr al-Dīn ar-Rāzī. The discussion focuses on the structure of Aristotelian science and the influence of metaphysics on the analysis of sensible phenomena. Rāzī assesses the epistemological and ontological principles underlying Avicenna’s interpretation of demonstrative science. Finding knowledge of essences and the necessary relations posited in demonstrative science problematic, Rāzī develops an alternative to Aristotelian science based on a theory of phenomenal knowledge. A preliminary analysis of the reception of Rāzī’s system is also conducted.